The Influence of Various Intrapersonal Factors of Pregnant Women on Efforts to Prevent the Occurrence of Maternal Death Risk - Hendra Yulita (PT FORMOSA CENDEKIA GLOBAL, 2023)
Indicators of maternal health services aimed at reducing maternal mortality include prenatal checks, deliveries by health services, and deliveries assisted by qualified health personnel. The purpose of pregnancy checks is to detect pregnancy disorders that can harm the mother and her fetus. Deliveries to health facilities include health centers, clinics, maternity wards, health workers and hospitals. The purpose of this study was to examine the effect of intrapersonal characteristics of pregnant women on efforts to prevent maternal mortality risk by using cross-sectional quantitative methods using primary and secondary data. The sample was 34 intrapersonal pregnant women who were sent questionnaires for 2020 data collection in Konawe Regency, where the maternal mortality rate is still high. The research locations were the Asinua Health Center and Anggalomoare Health Center because maternal deaths in childbirth are more widespread. Five intrapersonal characteristics of pregnant women were analyzed. Inferential analysis (Fisher's exact probability test) was used in this study. Maternal mortality risk prevention interventions are influenced by several intrapersonal factors, including the presence of pregnancy risk markers, maternal barriers to health services, satisfaction with midwifery services, as well as knowledge and attitudes about pregnancy risk markers